(untitled) (Вісник: Міжнародні відносини, 2025)
Background: This article explores the European Union’s approaches to assessing energy security through a system of indicators in the dynamic conditions of geopolitical changes. It investigates the transformation of their role, from ignored warning signals to key tools for crisis management. The relevance of the study is driven by the need to evaluate the effectiveness of EU policy in response to Russia’s energy blackmail and to identify new challenges following the bloc’s rejection of its energy carriers. Methods: The research is based on an analysis of the EU’s regulatory framework (the REPowerEU plan, relevant regulations), quantitative indicators from official sources (import dependency, diversification of suppliers, strategic reserves), and analytical reports from international institutions. A systemic approach is applied to assess the effectiveness of these indicators as preventive and operational tools in risk management. Results: It was found that until 2022, the indicators clearly signaled the EU’s critical dependence on Russia, but these warnings were ignored due to a lack of political will. Following the invasion, the indicators became the foundation for setting measurable goals (demand reduction, storage filling), monitoring, and market stabilization, which helped overcome the acute phase of the crisis. At the same time, new systemic vulnerabilities were identified: dependence on the global LNG market, supply chains for critical raw materials for the "green" transition, and the growth of cyber threats. Conclusions: The role of energy security indicators in the EU has evolved from a passive warning to an active crisis management tool. Despite the demonstrated resilience, the Union’s energy security remains dynamic and vulnerable. The existing monitoring system needs to be adapted to assess new geopolitical, technological, and raw material risks. Effective future management will require the development of new indicators that account for the complex nature of modern threats.